Shenahweum minutum (Hemiptera, Aphidoidea: Drepanosiphinae)—taxonomic position and description of sexuales - Wieczorek, Karina; Kanturski, Mariusz; Junkiert, Łukasz (Zootaxa, 2013)
The oviparous female and winged male of Shenahweum minutum (Davis) are described and illustrated in detail for the first time. Notes on distribution and host plants are presented as well as additional taxonomic data on the genus.